(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The industrial revolution 4.0 resulted in increased public demands for information disclosure on the activities carried out by the government. The public demanded that they be able to obtain information quickly and easily be accessed. Therefore, the government has required all public bodies to develop government. E-government can provide transparency of information on government activities. The availability of information transparency will make it easier for the public to respond, monitor, and evaluate the performance of the government, which will affect public satisfaction and ultimately have an impact on increasing public trust in the government because it can create good governance. This study aims to determine whether there is an effect of information transparency on the level of public trust in the government by using public satisfaction as a mediator variable. The type of research is explanatory with a sample of 100 Bandung residents. This research uses path analysis to analyze data The results showed that transparency affects public satisfaction. Satisfied citizens will ultimately have an impact on public trust in the government.